Financial Analysis of Various Small Scale Duck Business - Broto Wibowo (Indonesian Center for Animal Research and Development, 2016)
The development of duck farming in Indonesia significantly increases because of the higher demand of duck products. Duck farming has been developed throughout Indonesia, however it has not been evenly distributed because most of duck population are located in Java, which reaches 20,657,778 birds or 47.1% of the national duck population. Several business opportunities based on duck farming are: (1) Duck farming to produce consumption and hatching eggs; (2) Egg hatching to produce day old duck, either male or female duck; (3) Raising duck to produce pullet duck; (4) Fattening to produce male duck (three months old); (5) Production of salted egg; and (6) Egg distribution. These businesses are economically feasible.